Notification Of Customer Service In Computer Shop Using Android-Based Cloud Message Firebase - Amnah Amnah; Sulyono Sulyono; Ifan Reynaldi Utama (Prosiding International conference on Information Technology and Business (ICITB), 2019)
Notification is used to send a notification of current events to application users who are already using a particular system. So users do not get the floating message. Computer Store Application using Firebase cloud message is one form of application means that aims to help customers or application users in getting information about the goods being serviced. System development research using the Prototype method, this method is appropriate to be used to develop a software that was developed again. This method starts with gathering user needs. Use of Notification Services for Customers in Computer Stores is very appropriate to retain customers. The results showed that the Computer Shop Application using Firebase cloud message can help users get information on services in the Computer Shop quickly and accurately.Keywords: Mobile Application, Android, Firebase Cloud Massage, Prototype, Computer Service